2016
DOI: 10.1089/neu.2016.4456
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the Acutely Injured Spinal Cord to Vibration that Simulates Transport in Helicopters or Mine-Resistant Ambush-Protected Vehicles

Abstract: In the military environment, injured soldiers undergoing medical evacuation via helicopter or mine-resistant ambush-protected vehicle (MRAP) are subjected to vibration and shock inherent to the transport vehicle. We conducted the present study to assess the consequences of such vibration on the acutely injured spinal cord. We used a porcine model of spinal cord injury (SCI). After a T10 contusion-compression injury, animals were subjected to 1) no vibration (n = 7-8), 2) whole body vibration at frequencies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…While we had previously shown this therapy to be effective at improving behavioral recovery in a rodent model of thoracic and cervical SCI [ 12 , 15 ], we found that the magnesium chloride therapy did not reproduce the same promising therapeutic benefits in our pig model, either for improving locomotor recovery or increasing spared tissue at the injury site [ 22 ]. We have also used the pig model to evaluate the effect of wholebody vibration, which is applicable to individuals who have sustained an SCI and are being transported via air or road [ 21 ]. It was established that such vibration was not detrimental to the acutely injured spinal cord, and in fact in some ways may have even been beneficial [ 21 ].…”
Section: Applications Of the Porcine Sci Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…While we had previously shown this therapy to be effective at improving behavioral recovery in a rodent model of thoracic and cervical SCI [ 12 , 15 ], we found that the magnesium chloride therapy did not reproduce the same promising therapeutic benefits in our pig model, either for improving locomotor recovery or increasing spared tissue at the injury site [ 22 ]. We have also used the pig model to evaluate the effect of wholebody vibration, which is applicable to individuals who have sustained an SCI and are being transported via air or road [ 21 ]. It was established that such vibration was not detrimental to the acutely injured spinal cord, and in fact in some ways may have even been beneficial [ 21 ].…”
Section: Applications Of the Porcine Sci Modelmentioning
confidence: 99%
“…We have also used the pig model to evaluate the effect of wholebody vibration, which is applicable to individuals who have sustained an SCI and are being transported via air or road [ 21 ]. It was established that such vibration was not detrimental to the acutely injured spinal cord, and in fact in some ways may have even been beneficial [ 21 ].…”
Section: Applications Of the Porcine Sci Modelmentioning
confidence: 99%
See 3 more Smart Citations